Foraging activity and diet of the ant, Anoplolepis tenella Santschi (Hymenoptera: Formicidae), in southern Cameroon - Kuate, A.F.; Tindo, M.; Hanna, R.; Kenne, M.; Goergen, Georg E. (2008)
Anoplolepis tenella is a ground-nesting ant of the tropical forest zone of Central Africa, commonly associated with African root and tuber scale, Stictococcus vayssierei Richard, an emerging cassava pest. Understanding the ant’s foraging activity and diet breadth is an important step towards developing control measures against S. vayssierei. The present study was carried out in cassava fields in Awae II and Mengomo, southern Cameroon, during the short wet and dry seasons of 2006. Foraging activity of A. tenella was continuous during the circadian cycle and showed four peaks of activity; two during the day and two at night at both localities and in both seasons. Activity was greater at night than during the day, and greater in the wet than in the dry season. During the day, activity was significantly positively correlated with relative humidity, and negatively correlated with air temperature. During the night, it was positively correlated with relative humidity but not with air temperature at both localities. The diet of A. tenella consisted of solid items, mainly live prey (63.3 %) but also dead prey (36.7 %) and sugary secretions collected from various hemipterans. Stictococcus vayssierei was the most commonly tended hemipteran (98.5 %). Continuous foraging activity, omnivory and especially association with hemipterans are factors that favour the numerical dominance of A. tenella in cassava fields.